Spatial distribution of Ephemeroptera, Plecoptera, Trichoptera and Coleoptera (Insect) in a first order stream, montane forest, Junín, Peru - Sajamí Reymundo, Janet Isabel (2016)
The aim of this paper was to study the composition and spatial distribution of four orders of aquatic insects Ephemeroptera, Plecoptera, Trichoptera and Coleoptera (EPTC) in a first order stream, Chanchamayo, Peru. Sampling was done bimonthly from March 2013 to January 2014 in four lotic microhabitats: stones, gravel, moss and leaf litter from rifles. There were collected 7825 individuals grouped in 51 genera distributed in 27 families of EPTC, being the first records of aquatic insects in a first order stream of a Montane Forest in the Peruvian Central Andes. The microhabitat litter from rifles presented the highest abundance, richness and diversity. The most representative genera in terms of abundance throughout the basin were Farrodes (10.35%), Phylloicus (10.01%) and Heterelmis (6.07%). The family Elmidae was the most diverse with 11 genera. The non-parametric statistical test of Kruskall-Wallis for the richness, abundance and Shannon-Wiener´s diversity and Pielou´s equitability determined significant differences (p <0.05) between of microhabitats. The similarity analysis (ANOSIM) and clustering using the non-parametric method multidimensional scaling (nMDS) found differences between of microhabitats.